The Solar Neighborhood L: Spectroscopic Discovery of K Dwarfs Younger Than 1 Gyr and New Binaries within 30 pc - Hubbard-James, Hodari-Sadiki; Lesley, D. Xavier; Henry, Todd J.; Paredes, Leonardo A.; Nisak, Azmain H. (The Astronomical Journal, 2022)
As part of a comprehensive effort to characterize the nearest stars, the CHIRON echelle spectrograph on the CTIO/SMARTS 1.5 m telescope is being used to acquire high-resolution (R = 80,000) spectra of K dwarfs within 50 pc. This paper provides spectral details about 35 K dwarfs from five benchmark sets with estimated ages spanning 20 Myr–5.7 Gyr. Four spectral age and activity indicators are tested, three of which aligned with the estimated ages of the benchmark groups—the Na i doublet (5889.95 and 5895.92 Å), the Hα line (6562.8 Å), and the Li i resonance line (6707.8 Å). The benchmark stars are then used to evaluate seven field K dwarfs exhibiting variable radial velocities for which initial CHIRON data did not show obvious companions. Two of these stars are estimated to be younger than 700 Myr, while one exhibits stellar activity unusual for older K-dwarf field stars and is possibly young. The four remaining stars turn out to be spectroscopic binaries, two of which are being reported here for the first time with orbital periods found using CHIRON data. Spectral analysis of the combined sample of 42 benchmark and variable radial velocity stars indicates temperatures ranging from 3900 to 5300 K and metallicities from −0.4 < [Fe/H] < +0.2. We also determine for main-sequence K dwarfs. Ultimately, this study will target several thousand of the nearest K dwarfs and provide results that will serve present and future studies of stellar astrophysics and exoplanet habitability.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Orbits of M Dwarf Binaries Big and Small: Revealing Their Sizes and Shapes Via a Multi-Pronged Observing Campaign - Vrijmoet, Eliot; Henry, Todd; Tokovinin, Andrei; Dieterich, Serge; Horch, Elliott; Jao, Wei-Chun; Winters, Jennifer; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #205.10 in the session Binary Stellar System - iPoster Session.
Keywords: dept.phy; ⛔ No DOI found

The RKSTAR Concert — A RECONS Survey of the 5000 Nearest K Dwarfs - Henry, Todd; Casetti-Dinescu, Dana; Horch, Elliott; Hubbard-James, Hodari-Sadiki; Jao, Wei-Chun; Lesley, D. Xavier; Paredes, Leonardo; Shea, Melissa; Sutherland, Torrie; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #305.15 in the session Stars, Cool Dwarfs, Brown Dwarfs — iPoster Session.
Keywords: dept.phy; ⛔ No DOI found